Building an ontological knowledgebase for bridge maintenance. (April 2019) - Ren, Guoqian; Ding, Rui; Li, Haijiang
Highlights: Demonstrate that the process of traditional bridge maintenance lacks effective computer-aided tools. State how ontology provides potentials for integrating multiple domain knowledge into a knowledge model. Propose a semantic approach to help build a knowledge base for bridge maintenance that offers better deliverables. The selection of material suppliers and the arrangement of events are holistically considered through reasoning-based knowledge processing. Abstract: The operation stage has the biggest potential value in the bridge life cycle management, and it often critically influences the overall cost of the bridge. As such, changes in the efficiency of the project's operation stage could be of significant benefit to the overall project. However, current approaches in the operation stage often lack the effective support of computer-aided tools. This research presents a holistic method based on an ontology to achieve automatic rule checking and improve the management and communication of knowledge related to bridge maintenance. The developed ontology can also facilitate a smarter decision-making process for bridge management by informing engineers of choices with different considerations. Three approaches; semantic validation, syntactical validation, and case study validation, have been adopted to evaluate this ontology and demonstrate how the developed ontology can be used by engineers when dealing with different issues. The results showed that this approach can create a holistic knowledge base that can integrate various domain knowledge to enable bridge engineers to make more comprehensive decisions rather than a single objective-targeted delivery.